A progress on equality matters: A law which prohibits salary discrimination - Palma Quiñones, Tatiana Patricia (2020)
This paper aims to analyze the recent regulations related to salary equality between men and women. We will make a feedback from a practical and legal approach to this regulation and we will evaluate what would be the next legislative impulses that must be given in the future to achieve the long-awaited equality in the working world.